38.4k views
5 votes
Pls i need it like now

Pls i need it like now-example-1

1 Answer

1 vote
You need to put the x or y value in the other equation ;
For example excersize a
It given that
Y=x^2+3x-1
Then you put it on the first equation :
x+x^2+3x-1=4
And then you solve it
x+x^2+3x-1-4=0
4x+x^2-5=0
We will make the order to seem easier
x^2+4x-5=0
x1=-5
x2=1
Then you put the x1,2 that you found on the second equation :
y=(-5)^2+3*(-5)-1=9
y=1^2+3*1-1=3
For summary :
x1=-5
x2=1
y1=9
y2=3

User Buu
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.